An analysis of real-time traffic congestion optimisation through VTL in VANETs. (2nd June 2022) - Choudhary, Parul; Dwivedi, Rakesh K.; Singh, Umang
Traffic congestions are a daunting phenomenon that affects thousands of people worldwide in their everyday lives. Owing the rapid proliferation of technologies, the demand for VANET technology is increasing expeditiously to create an environment for a Virtual Traffic Light (VTL) to minimise traffic congestion. The replacement of conventional physical traffic light systems with VTL is cost-efficiently achieved across vehicle networks. In this paper, we summarise the recent state-of-the-art methods of VANETs by discussing the importance of Virtual Traffic Light in VANET, its architecture and real-life applications. Further, work is focused on challenges, characteristics and related domains of allied VANETs applications by filling the gaps of existing surveys along with the latest trends incorporating the concept of VTL. This attempt presents the effectiveness of virtual traffic by including recent work in real scenarios according to research findings. This paper offers a systematic review of current VTL methodologies that promise to show an impactful result in the future. Finally, this attempt comprehensively covers the entire VANET system and highlights certain research gaps of VTL that are still left to be explored. This work will support researchers of this domain by analysing the literature on VTL in VANET during the period 2007-2019.